Letter to the Editor in response to 'Parental attachment and depressive symptoms in pregnancies complicated by twin-twin transfusion syndrome: a cohort study' - Georges Rameh; Pia Tohme; Rudy Abi-Habib; Gihad E Chalouhi (BMC, 2021)
Abstract Twin-twin transfusion syndrome is a highly morbid condition that can affect parental attachment and depression risk. Studies addressing this rare condition are hard to conduct and thus lacking in the literature. In this letter to the editor, we acknowledge the article of Mackie et al. entitled "Parental attachment and depressive symptoms in pregnancies complicated by twin-twin transfusion syndrome: a cohort study" to be of high importance and impact, but would like to discuss the extent of its conclusions, and push towards bigger studies in this field.